The Implementation of Disaster Curriculum Toward Disaster Preparedness Campus at Syiah Kuala University - Ahmad Nubli Gadeng; Enok Maryani; Epon Ningrum; Iwan Setiawan (Department of Geography Education, University of Jember, 2022)
The earthquake and tsunami disasters in Aceh Province, Indonesia led to several injuries, deaths, unfound bodies, and high property losses on 26 December 2004. This hazardous period has reportedly become a valuable case for Syiah Kuala University, where various solutions are being considered for eradicating subsequent occurrences. Therefore, this study aims to determine the implementation patterns of the disaster curriculum developed and applied at Syiah Kuala University, to achieve a DPC (Disaster Preparedness Campus) reputation and enhance DP (Disaster Preparedness) among community members, especially students. A qualitative verification method outlined as a description was used, due to being an inductive approach to the entire experimental process. Data collection was also carried out through observation and literature review, as well as several interviews with the following, (1) The head of the technical implementation unit general course of Syiah Kuala University, (2) The coordinator and lecturer of disaster and environmental knowledge course, and (3) The students of Syiah Kuala University studying the course. After this process, a Delphi method was used to analyze the data obtained, with the outcomes confirmed by a competent expert. Based on the results, three important steps were found to improve disaster preparedness among the people of Aceh and Syiah Kuala University students, namely (1) The establishment of the Tsunami Disaster Mitigation Research Center in 2006, (2) The establishment of the Master Program Study of Disaster Science in the university's Postgraduate Program in 2010, and (3) Development of the general course of disaster knowledge and environment in 2016, which was a compulsory requirement for all students from various faculties, departments, and programs. This indicated that Syiah Kuala University was the first campus to mandate a disaster science course in Indonesia. These results are expected to improve disaster preparedness for students, with Syiah Kuala University becoming a DPC (Disaster Preparedness Campus) in Indonesia. Keywords : Implementation; Disaster Curriculum; Disaster Preparedness Campus Copyright (c) 2022 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License